Требования и этапы создания электронной паспортной системы Украины - Сиренко, А. Ю. (ХНУРЭ, 2009)
A e-passport is a combined paper and electronic identity document that uses biometrics to authenticate the identity of travelers. The passport's critical information is stored on a tiny RFID computer chip. The Global Interoperability of system is achieved by Public Key Infrastructure.